تقنيات المحاسبة القضائية: أداة فعالة للمدقق الخارجي في مكافحة الاحتيال في البيانات المالية: Forensic Accounting Techniques: An Effective Tool for the External Auditor in detecting fraud in financial statements - عبد المجيد بن العربي (Journal of North African Economies, 2025)
The study aims to determine the impact of using external auditors for forensic accounting techniques in detecting fraud in financial data. The problem lies in identifying the added value that can be achieved by the external auditor through the use of forensic accounting techniques in fraud detection. Using the descriptive-analytical approach, we addressed fraud in financial data, the responsibility of the auditing profession towards it, and the forensic accounting techniques used to detect it. A main hypothesis was formulated to study the impact of using external auditors for forensic accounting techniques on fraud detection in financial data. To gather the necessary information and analyze opinions, a questionnaire was distributed to a random sample of 91 professionals and university professors. The study concluded that there is an effective impact of using forensic accounting techniques by external auditors in detecting fraud in financial data.